Nilai Keimanan Agama Islam Dalam Kumpulan Puisi Seribu Masjid Satu Jumlahnya Karya Emha Ainun Nadjib - Sahli (ISLAMICA, 2016)
Poetry as one of the genre of literature that has unique characteristics express ideas, theories, thinking systems, and of course the mood of the author so that the audience can capture the author's inner wealth through his poems. Though written in short sentences, poetry contains vast contents and contains a deep message for the audience. The teachings of Islam are one of the most interesting things to pour out in poetry. Many poets are trying to display the teachings of Islam in the form of poetry. In the last decade, the development of Sufismpoetrythemed deity and containing the breadth of religious teachings is increasing. Human experience in the process of searching and finding Al Khalik is a reflection object that is quite interesting and feels actual for the poet. Evidently, some entity who try to actualize their inner experience of this problem. In this paper will be displayed one of the teachings of Islam that is the values of faith in the form of poetry. Islam as a set of values and rules that provide guidance to humans in associating with God has colored the style of poems written by Indonesian poets.